2018
DOI: 10.1111/ajt.14548
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with perceived donation-related financial burden among living kidney donors

Abstract: The perception of living kidney donation-related financial burden affects willingness to donate and the experience of donation, yet no existing tools identify donors who are at higher risk of perceived financial burden. We sought to identify characteristics that predicted higher risk of perceived financial burden. We surveyed 51 living kidney donors (LKDs) who donated from 01/2015 to 3/2016 about socioeconomic characteristics, predonation cost concerns, and perceived financial burden. We tested associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…15 Our finding that sex-related differences in living donation persisted after adjustment for differences in ESRD between women and men suggests the importance of other factors including differences in the financial implications of donation, attitudes toward donation, or societal expectations of donation between women and men contribute to the sex-related difference in living donation. 5,15 Our findings also draw further attention to financial barriers to living donation (see recommendations from the American Society of Transplantation Living Donor Community of Practice consensus conference 16 and other recent publications 17,18 for a comprehensive overview of this issue). The finding that income had a greater effect on donation from men should be interpreted with the knowledge that living donors and recipients are usually from the same socioeconomic background and, in many cases, the same household.…”
Section: Discussionsupporting
confidence: 53%
“…15 Our finding that sex-related differences in living donation persisted after adjustment for differences in ESRD between women and men suggests the importance of other factors including differences in the financial implications of donation, attitudes toward donation, or societal expectations of donation between women and men contribute to the sex-related difference in living donation. 5,15 Our findings also draw further attention to financial barriers to living donation (see recommendations from the American Society of Transplantation Living Donor Community of Practice consensus conference 16 and other recent publications 17,18 for a comprehensive overview of this issue). The finding that income had a greater effect on donation from men should be interpreted with the knowledge that living donors and recipients are usually from the same socioeconomic background and, in many cases, the same household.…”
Section: Discussionsupporting
confidence: 53%
“…A recent report found that donors who perceived donation-related financial burden were less likely to have an income above the median in their residential area. 30 In a separate study, candidates told family members and friends that they were willing to donate but that they were concerned about the potential lost income. 31 Prior cost estimates vary, with median out-of-pocket costs ranging between $179 and $821 (not accounting for productivity losses).…”
Section: Discussionmentioning
confidence: 99%
“…There were disparities in donor-recipient concordance as well; while 95% of non-Hispanic White children were likely to receive a kidney from a non-Hispanic White donor, only 56% of Asian recipients had Asian donors. Socioeconomic factors that allow individuals to step forward as kidney donors are a major contributor ( 37 ). Literature also supports that deceased donor transplant rates are lower among Black children compared to Whites ( 38 ).…”
Section: The Impact Of Systemic Bias and Racism On Ckd And Transplant...mentioning
confidence: 99%